Response of Superovulation by Using FSH (Follicle Stimulating Hormone) and Sex Determination of Embryos Using PCR in Pesisir Cows of West Sumatra - Afriani, Tinda; Sayful, Fery Lismanto; Sumedi, Sumedi; Putra, Dino Eka; Purwati, Endang (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
This study was conducted to determine the response of superovulation by giving 16 ml dosage of FSH hormone to female Pesisir cattle. The estrus schedule of 15 Pesisir cows was set by inserting CIDR (Controlled Internal Drug Release) into the vagina for 12 days. At day 10, all cattles were injected with FSH for three consequent days but with decreasing dosage. On the 3rd day, FSH injection was accompanied by PGF2α injection and CIDR was removed. The detection of estrus was performed at day 13. Natural mating was proceeded after the estrus signs visible. Collection of donor embryos was done on the 6th and 8th day after mating. The variables measured were the response of superovulation, total number of corpus luteum, number of embryos and sex ratio. The results obtained were all Pesisir cows responded to superovulation. The average number of of corpus luteum and embryoes per cow were 5.93±3.17 and —–, respectively, while the total of transferable embryoes were 90, with an average of 6.00 or 61.64%. The sexing of embryoes obtained in this study from 146 embryoes awere 76.03% males (111 embryoes) and 23.97% females (35 embryoes). Based on total of transferable embryoes, there were 51.37% male embryos and 11.28% of females embryos. The result of this study showed that the sex ratio of male embryos was higher than female embryos.